Re-Assessment of Strains from Aspergillus Section Fumigati and Description of Two Unrecorded Species from Korea - Anbazhagan Mageswari; Daseul Lee; Jae Sung Lee; Le Dinh Thao; Donghun Kang; Seung-Beom Hong (Mycobiology)
The Aspergillus section Fumigati comprises economically significant fungi, with its teleomorphic species classified under the genus Neosartorya. Several species within this genus produce a variety of secondary metabolites, offering significant potential for applications in agriculture, medicine, and pharmaceuticals. In this study, 69 strains from the section Fumigati, originating from Korea were taxonomically re-assessed using a combined analysis of their partial β-tubulin and Calmodulin gene sequences, supported along with morphological characteristics. The 69 strains were found to be distributed among 15 species which are now confirmed to be originally isolated from Korea. Of them, 13 species have been previously reported in Korea (A. assulatus, A. coreanus, A. fennelliae, A. fischeri, A. fumigatus, A. hiratsukae, A. laciniosus, A. lentulus, A. neoglaber, A. quadricinctus, A. spinosus, A. turcosus, and A. udagawae), and two species (A. solicola and A. thermomutatus) represent new findings for this region. This study presents a detailed characterization of these two previously unexplored species, highlighting their distinct morphological traits, gene sequence variations, and occurrence in ecological niches in Korea.